Effects of a Submesoscale Oceanographic Filament on Zooplankton Dynamics in the Arctic Marginal Ice Zone - Kaiser, Patricia; Hagen, Wilhelm; von Appen, Wilken-Jon; Niehoff, Barbara; Hildebrandt, Nicole; Auel, Holger (Frontiers in Marine Science, 2021)
Submesoscale structures, characterized by intense vertical and horizontal velocities, potentially play a crucial role in oceanographic dynamics and pelagic fluxes. Due to their small spatial scale and short temporal persistence, conditions for in situ measurements are challenging and thus the role of such structures for zooplankton distribution is still unclear. During RV Polarstern expedition PS107 to Arctic Fram Strait in July/August 2017, a submesoscale filament was detected, which initiated an ad hoc oceanographic and biological sampling campaign. To determine zooplankton taxonomic composition, horizontal and vertical distribution, abundance and biomass, four MultiNet hauls (depth intervals: 300-200-100-50-10-0 m) were taken in cross-filament direction. Zooplankton data were evaluated in context with the physical-oceanographic observations of the filament to assess submesoscale physical-biological interactions. Our data show that submesoscale features considerably impact zooplankton dynamics. While structuring the pelagial with distinct zooplankton communities in a vertical as well as horizontal dimension, they accumulate abundance and biomass of epipelagic species at the site of convergence. Further, high-velocity jets associated with such dynamics are possibly of major importance for species allocation and biological connectivity, accelerating for instance processes such as the ‘Atlantification’ of the Arctic. Thus, submesoscale features affect the surrounding ecosystem in multiple ways with consequences for higher trophic levels and biogeochemical cycles.